2010
DOI: 10.1007/s00276-010-0677-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative anatomical study of male pelvic autonomic plexus and its clinical potential in rectal resection

Abstract: The pelvic autonomic nerves innervate the pelvic viscera, and carry a high risk of damage during surgery. This high risk has been ascribed to the complex interrelationship of pelvic paravisceral structures and the difficulty in identifying particular structures, despite the fact that the anatomic characteristics of the pelvic autonomic plexus have been well documented. We dissected ten male embalmed adult cadavers with particular attention to the quantitative parameters of the pelvic plexus and its subsidiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The tiny neurogenic pathways could be visually identified in up to 45% on each pelvic side and were found tracing the pelvic floor in posterolateral (4–5 and 7–8 o’clock lithotomy position) to anterolateral direction on the supralevatoric pelvic sidewall (3 and 9 o’clock lithotomy position) up to the IRP. Cadaver dissection via non-surgical approach demonstrated variations of the branches in terms of number (three to six nerve fibers), diameter (up to 1.1 ± 0.2 mm) and length (up to 37.3 ± 13.6 mm) ( 2 ). Recently, video-endoscopic supported cadaver dissections with a “bottom up” approach revealed them to reach the most distal rectum constituting nerve fibers to the IAS ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The tiny neurogenic pathways could be visually identified in up to 45% on each pelvic side and were found tracing the pelvic floor in posterolateral (4–5 and 7–8 o’clock lithotomy position) to anterolateral direction on the supralevatoric pelvic sidewall (3 and 9 o’clock lithotomy position) up to the IRP. Cadaver dissection via non-surgical approach demonstrated variations of the branches in terms of number (three to six nerve fibers), diameter (up to 1.1 ± 0.2 mm) and length (up to 37.3 ± 13.6 mm) ( 2 ). Recently, video-endoscopic supported cadaver dissections with a “bottom up” approach revealed them to reach the most distal rectum constituting nerve fibers to the IAS ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The last columns depict the identifiability and level of agreement with positional references, anatomist, and radiologistNerve/ plexusRecords included in quantitative synthesisMain positional referenceIdentifiability (%) a Conform positional reference (%) b Level of agreement anatomist (Likert score 2)Level of agreement radiologist (Likert score 2)Lumbosacral plexusNANA20 (100)NA20 (100)20 (100)Sacral nervesNANA20 (100)NA20 (100)20 (100)Obturator nerve2 [11, 12]Appearance lateral to confluence of the internal and external iliac vein20 (100)20 (100)20 (100)20 (100)Sympathetic trunk4 [1316]Entrance pelvis from either side of the lumbar spine dorsal from common iliac vein to course medial to sacral foramina19 (95)19 (100)19 (100)19 (100)Superior hypogastric plexus12 [7, 1626]Division at or just below the level of the sacral promontory14 (70)14 (100)14 (100)14 (100)Hypogastric nerve12 [7, 16, 19, 21, 2532]Course just medial to internal iliac vessels16 (80)16 (100)16 (100)16 (100)Inferior hypogastric plexus17 [7, 16, 21, 2538]Ureter crosses, just before entering the bladder, anterior to the IHP…”
Section: Resultsmentioning
confidence: 99%
“…Few papers have been published, owing to the high cost and limited application of the method. A study of 15 patients undergoing rectal operations by robotic surgery showed a similar short‐term outcome with no complications compared with laparoscopic surgery . Meta‐analysis comparing laparoscopic surgery and robotic surgery has demonstrated the latter method to benefit from less blood loss, shorter hospital stay and lower rate of intra‐operative conversion, especially when TME principle was followed .…”
Section: Advanced Rectal Cancermentioning
confidence: 99%